Metabolic Syndrome Prevalence and Reduction in Inmates Prescribed Antipsychotic Medications. (April 2017) - Reeves, Rusty; Tamburello, Anthony; DeBilio, Lisa
The principal aim of this study was to establish whether a metabolic monitoring program implemented for second-generation antipsychotic medications (SGAs) was associated with any reduction in the prevalence of metabolic syndrome in adult inmates treated with antipsychotic medications in the New Jersey Department of Corrections. The average prevalence of metabolic syndrome in those prescribed SGAs decreased from 17.9% during the years before metabolic monitoring to 14.3% during the years of monitoring. The number of patients prescribed antipsychotic medication decreased a net 35% over 9 years of the study. We conclude that metabolic monitoring was one of the several administrative interventions over the study period that reduced the unnecessary exposure of inmates to the risks of antipsychotic medications.